2008
DOI: 10.1111/j.1468-1293.2008.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of new 625 mg nelfinavir formulation during pregnancy and postpartum

Abstract: ObjectivesOur objective was to evaluate the pharmacokinetics of nelfinavir (NFV) (625 mg tablets) 1250 mg twice daily during pregnancy and postpartum. MethodsThe participants were HIV-1-infected pregnant women enrolled in P1026s and receiving NFV (625 mg tablets) 1250 mg twice daily as part of routine clinical care. Intensive steady-state 12-h NFV pharmacokinetic profiles were performed during pregnancy and postpartum. The target NFV area under the plasma concentration-time curve (AUC 0-12 ) was ! 10th percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…Many experts, however, consider it to be reasonable to increase the dose of certain PI’s during the third trimester when viral load remains unsuppressed in the setting of good medication adherence. 25 Whether or not such dose increases might have reduced the loss of suppression in this cohort is unknown. We believe our findings warrant further study in trials where information on medication adherence, pharmacokinetics, and resistance can be obtained.…”
Section: Discussionmentioning
confidence: 92%
“…Many experts, however, consider it to be reasonable to increase the dose of certain PI’s during the third trimester when viral load remains unsuppressed in the setting of good medication adherence. 25 Whether or not such dose increases might have reduced the loss of suppression in this cohort is unknown. We believe our findings warrant further study in trials where information on medication adherence, pharmacokinetics, and resistance can be obtained.…”
Section: Discussionmentioning
confidence: 92%
“…In the twelve included studies [10, 32, 33, 35, 36, 56-62], reported average cord to maternal concentration ratios fluctuated widely from 0.0 to 0.49; likewise, cord blood nelfinavir concentration averages varied from 0.0 to 0.27 mg/L. Concentrations of nelfinavir were frequently undetectable in both maternal and cord samples, and the studies that reported higher averages tended to exclude these undetectable concentrations from their summary measure.…”
Section: Resultsmentioning
confidence: 99%
“…5-9 For some of these drugs, including lopinavir, atazanavir and nelfinavir, use of increased doses in pregnancy has been shown to result in plasma concentrations equivalent to those seen in nonpregnant adults receiving standard dosing. 31-33 Two randomized studies of standard versus increased dose lopinavir in pregnancy suggest that increased lopinavir doses may be beneficial for pregnant women with a detectable viral load at initiation of treatment in pregnancy or with detectable lopinavir resistance mutations.…”
Section: Discussionmentioning
confidence: 99%